Ultrafast Processes in Graphene: From Fundamental Manybody Interactions to Device Applications. Issue 11 (23rd August 2017) - Winnerl, Stephan; Mittendorff, Martin; König‐Otto, Jacob C.; Schneider, Harald; Helm, Manfred; Winzer, Torben; Knorr, Andreas; Malic, Ermin
Abstract: A joint experiment‐theory investigation of the carrier dynamics in graphene, in particular in the energetic vicinity of the Dirac point, is reviewed. Radiation of low photon energy is employed in order to match the intrinsic energy scales of the material, i.e. the optical phonon energy (∼200 meV) and the Fermi energy (10‐20 meV), respectively. Significant slower carrier cooling is predicted and observed for photon energies below the optical phonon energy. Furthermore, a strongly anisotropic distribution of electrons in k ‐space upon excitation with linearly polarized radiation is discussed. Depending on photon energy, the anisotropic distribution decays either rapidly via optical phonon emission, or slowly via non‐collinear Coulomb scattering. Finally, a room temperature operated ultra‐broadband hot‐electron bolometer is demonstrated. It covers the spectral range from the THz to visible region with a single detector element featuring a response time of 40 ps. Abstract : The carrier dynamics in graphene is investigated in a joint experiment‐theory study, with a particular focus on optical excitations at low energies. The role of carrier‐phonon and carrier‐carrier scattering is clearly disentangled and a twofold behavior for carrier‐carrier scattering is revealed: (i) fast collinear scattering and (ii) comparably slow non‐collinear scattering. Furthermore fast ultrabroadband detectors, covering the range from THz to visible, are demonstrated.